Potential of N2 Gas Flushing to Hinder Dairy-Associated Biofilm Formation and Extension - Munsch-Alatossava, Patricia; Alatossava, Tapani (Frontiers in Microbiology, 2020)
Worldwide, the dairy sector remains of vital importance for food production despite severe environmental constraints. The production and handling conditions of milk, a rich medium, promote inevitably the entrance of microbial contaminants, with notable impact on the quality and safety of raw milk and dairy products. Moreover, the persistence of concentrations of microorganisms (especially bacteria and bacterial spores) in biofilms (BFs) present on dairy equipment or environments constitutes an additional major source of milk contamination at pre/processing stages: in dairies, BFs represent a major concern regarding the risks of disease outbreaks and are often associated with significant economic losses. One consumption trend towards “raw or low-processed foods” combined with current trends in food production systems, which tend to have more automation and longer processing runs with simultaneously more stringent microbiological requirements, necessitate the implementation of new and obligatory sustainable strategies to respond to new challenges regarding food safety. Here, in light of studies, performed mainly with raw milk, that considered dominant “planktonic” conditions, we re-examine the changes triggered by cold storage alone or combined with nitrogen gas (N2)- flushing on bacterial populations, and discuss how the observed benefits of the treatment could also contribute to limiting BF formation in dairies.